2010
DOI: 10.1371/journal.pone.0013607
|View full text |Cite
|
Sign up to set email alerts
|

Regional Mucosa-Associated Microbiota Determine Physiological Expression of TLR2 and TLR4 in Murine Colon

Abstract: Many colonic mucosal genes that are highly regulated by microbial signals are differentially expressed along the rostral-caudal axis. This would suggest that differences in regional microbiota exist, particularly mucosa-associated microbes that are less likely to be transient. We therefore explored this possibility by examining the bacterial populations associated with the normal proximal and distal colonic mucosa in context of host Toll-like receptors (TLR) expression in C57BL/6J mice housed in specific patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 30 publications
5
102
1
2
Order By: Relevance
“…Previous results have shown differences in composition of the microbiota along the length of the gut, in the mouse (Wang et al, 2010), chicken (Rehman et al, 2007) and humans (Costello et al, 2009). Both host diet and phylogeny influence fecal bacterial diversity, as shown by Ley et al (2008) who based on the composition of the feces, showed that herbivores generally clustered into two groups corresponding to foregut and hindgut fermenters.…”
Section: Discussionmentioning
confidence: 89%
“…Previous results have shown differences in composition of the microbiota along the length of the gut, in the mouse (Wang et al, 2010), chicken (Rehman et al, 2007) and humans (Costello et al, 2009). Both host diet and phylogeny influence fecal bacterial diversity, as shown by Ley et al (2008) who based on the composition of the feces, showed that herbivores generally clustered into two groups corresponding to foregut and hindgut fermenters.…”
Section: Discussionmentioning
confidence: 89%
“…21,22 The endotoxemia associated with a high-fat diet could initiate myenteric inducible NOS activation, known to increase in neurons after the systemic administration of LPS, 56 and can induce an overproduction of NO in nitrergic neurons, leading to oxidative stress and apoptosis. 42,57 This will be the focus of our future studies as we continue to understand the mechanisms of a HFDinduced nitrergic enteric neuronal degeneration and delayed colonic transit.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Gut microbial products signal through the pathogen recognition Toll-like receptor (TLR) family. In the murine enteric nervous system, TLR4 expression is maximal in the distal colon 21 and TLR3, 4, and 7 have been shown to be expressed in myenteric neurons and glia cells. 22 TLRs have been implicated in neuronal apoptosis, 23 and excess TLR4 activation by lipopolysaccharide (LPS) activates proinflammatory pathways and cytokine release within enteric neurons.…”
Section: Methodsmentioning
confidence: 99%
“…The type strain (ATCC 29148) of Bacteroides thetaiotaomicron only has 6.3 Mb genome sequence, but these genes can code 226 predicted glycoside hydrolases, 163 digesting starch proteins and 15 polysaccharide lyases [6]. Band B from KKAy, is similar with a series of uncultured bacteria which are beneficial for mice to express TLR4 on intestinal mucosa [8]. TLR4 triggers the activation of kinase cascades and stimulates signaling pathways of inflammation in cells for prompted insulin resistance [17].…”
Section: Discussionmentioning
confidence: 99%